2012
DOI: 10.1136/annrheumdis-2011-200738
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and factor XIII A-subunit genotypes interactively influence C-reactive protein levels during inflammation

Abstract: Objective Fibrinogen is a target of autoimmune reactions in rheumatoid arthritis (RA). Fibrin(ogen) derivatives are involved in infl ammatory processes and the generation of a stable fi brin network is necessary for suffi cient infl ammation control. As the density and stability of fi brin networks depend on complex interactions between factor XIIIA (F13A) and fi brinogen genotypes, the authors studied whether these genotypes were related to C-reactive protein (CRP) levels during acute-phase reactions. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…The expression of FXIII-A specific mRNA in a number of monocyte-derived macrophages including tumor macrophages, histocytes, dendritic reticulum cells, perivascular dendritic macrophages, and dermal dendrocytes was demonstrated, and their responsibility for the FXIII-A synthesis was strongly suggested [6,8,12,15,[22][23][24][25]. It was also observed that induction of monocytes differentiation into antigen presenting dendritic cells resulted in highly elevated FXIII-A expression, and its crucial role by fibrin crosslinking in this transformation was suggested.…”
Section: Fxiii-a In Inflammatory Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of FXIII-A specific mRNA in a number of monocyte-derived macrophages including tumor macrophages, histocytes, dendritic reticulum cells, perivascular dendritic macrophages, and dermal dendrocytes was demonstrated, and their responsibility for the FXIII-A synthesis was strongly suggested [6,8,12,15,[22][23][24][25]. It was also observed that induction of monocytes differentiation into antigen presenting dendritic cells resulted in highly elevated FXIII-A expression, and its crucial role by fibrin crosslinking in this transformation was suggested.…”
Section: Fxiii-a In Inflammatory Processesmentioning
confidence: 99%
“…The density and stability of fibrin networks depend on FXIIIA. In the study conducted by Hopped et al [23], FXIII-A gene variants modulating inflammation by influencing fibrin crosslinking were identified. These haemostatic gene variants as novel genetic determinants of C-reactive protein (CRP) in inflammatory process were considered.…”
Section: Fxiii-a In Inflammatory Processesmentioning
confidence: 99%
“…"positiver feed forward loop" zwischen inflammatorischer und Gerinnungsaktivierung [1]. Hier konnten wir kürzlich genetische Polymorphismen im Faktor XIII-A und Fibrinogen alpha sowie beta identifizieren, die auf eine deutliche Beziehung zwischen CRP-Spiegel und dem Grad der Entzündung hinweisen [2]. [4].…”
Section: Einleitung ▼unclassified
“…Die erhöhten Inzidenzen von venösen Verschlußereignissen ( • ▶ Tab. 1) wurde kürzlich für die meisten entzündlich-rheumatischen Erkrankungen im Vergleich zu Gesunden umfassend in einer Metaanalyse publiziert [6] 1,8 (1) 1,0 (2) 6,7 verordnet werden. Aus rheumatologischer Sicht muss bei entzündlich-rheumatischen Erkrankungen auf das erhöhte Blutungsrisiko unter den traditionellen NSAR hingewiesen werden und nach Möglichkeit Analgetika sowie Coxiben der Vorzug zu geben.…”
Section: Einleitung ▼unclassified
“…As CRP levels are critically influenced by a multitude of environmental factors, which are nearly uncontrollable, we used a time-averaged approach including all CRP measurements and adjusted for non-independent observations. 19 Analyses were performed on 639 patients with a total of 2333 CRP measurements (number of presentations: one (n=72), two (n=147), three (n=103), four (n=98), more than four (n=219)). Five hundred and sixty-five patients (88%) were of German origin and the other women were of Middle East and Asian origin.…”
Section: Study Populationmentioning
confidence: 99%